Growth and Yield Performance of Green Capsicum (Capsicum Annuum L.) As Influenced by Vermicompost Application Grown at Rooftop Of Chandpur Area (Journal of Biodiversity Conservation and Bioresource Management, 2022)
A pot experiment was conducted during rabi season during 2020-21 at a rooftop of Chandpur 150 MW Combined Cycle Power Plant (CCPP) Area in Chandpur Sadar upazila under Chandpur district to study the impact of different dosages of vermicompost (VC) on the growth and yield parameters of green capsicum plants (Capsicum annuum L.). It was laid out in a randomized complete block design (RCBD) with three replications each of six treatments viz. T1: 0 ton VC ha-1 (control), T2: 2.5 ton VC ha-1, T3: 5 ton VC ha-1, T4: 7.5 ton VC ha-1, T5: 10 ton VC ha-1, and T6:15 ton VC ha-1. Results revealed that maximum plant height (38.53 cm), number of leaf plant-1 (80), and highest number of branches plant-1 (6) were recorded in T5 followed by T3. The highest values for rest of the growth and yield parameters were found from the plant receiving VC at the rate of 5 ton ha-1 (T3), such as, longest leaf per plant (12.84 cm), highest number of branches plant-1 (6), maximum girth (3.53 cm), maximum number of fruits plant-1(7), average fruit weight (44.75 g fruit-1), maximum weight of fresh (320.28 g fruits plant-1) and dry (4.43 g fruits plant-1); and maximum total fresh (109.40 g) and dry weight (21.03 g) of plants. Highest fruit length (18.97 cm) and diameter of fruit (7.30 cm) were recorded in T5 and T4, respectively. Almost all of the growth and yield parameters were observed lowest in control (T1). Study indicates that supreme dose of VC 15 ton ha-1 in T6 yielded lower performance compare to 10 and 5 ton VC ha- 1. Considering the overall performance, it may be concluded that vegetative growth and yielding capacity of green capsicum plants can be boosted up by applying vermicompost at the rate of 10 ton ha-1 and 5 ton ha-1, respectively. This new information will be beneficial for growers, researcher and relevant workers.J. Biodivers. Conserv. Bioresour. Manag. 2021, 7(2): 13-22